A luminescent silver–phosphine tetragonal cage based on tetraphenylethylene. Issue 4 (23rd December 2015) - Feng, Juan; Yao, Liu; Zhang, Jianyong; Mu, Yingxiao; Chi, Zhenguo; Su, Cheng-Yong
Abstract : A phosphine-based tetragonal cage emits strong fluorescence both in dilute solutions and in aggregated states, showing response towards anions/olefin compounds. Abstract : A novel phosphine-based tetragonalAg4 L2 cage has been assembled from a tetraphenylethylene (TPE)-based tetraphosphine and Ag + ions. The cage structure is maintained both in solutions and in the solid state.Ag4 L2 emits strong fluorescence not only in dilute solutions but also in aggregated states. The turn-on fluorescence of TPE-P4 in dilute solutions is attributed to the formation ofAg4 L2 .Ag4 L2 shows potential as a fluorescent sensor towards anions and olefin compounds, which arises from binding of the guest anions/olefin compounds by its labile silver centres.